Construção do teste de aptidão criativa - TAC: forma experimental - Rosas, Argentina Carlos da Silva (1978)
The present work describes the construction of a psycholopical instrument to be used in the evaluation of creative behavior - the Test of Creative Aptitude. The Test was designed for use by professional counselors and school psychologists working in Brazil. The theoretical introduction to this report lays out the psychological bases of creativity, giving particular emphasis to relations with theories of personality and cognition. Following this, the author presents a detailed discussion of the development of the instrument from initial pilot studies to its present form o Throughout with care was given to demonstrate reliability and construct validity of the measure. Subjects in the present study were public and private school students in Recife, Brazil. Factor-analytic results with other measures used as marker variables indicated the presence of three dimensions in the instrument: Factor I, labelled Convergent Production; Factor it, Flexibility; and Factor III, Originality. Further analysis reveled that these factors are all normally distributed. A Cronbach- for the instrument was calculated as 0.72, indicating a substancial degree of homogeneity. A stepwise multiple regression analysis was performed to indicate the test itens with the total score. This procedure yielded itens which were most representative of the test as a whole, and as such would be selected for the final form ot the instrument. A criticism is made of the scoring technique and suggestions are proposed for improving the measurement in the future. The present study suggests the need for further conceptual clarification regarding basic theoretical notions of creativity. Further studies are recommended to standardize and establish the external validity ot the test of Creative Aptitude.